2019
DOI: 10.5815/ijisa.2019.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Application of Particle Swarm based Neural Network to Predict Scour Depth around the Bridge Pier

Abstract: Scour around the bridge pier is one of the major factors which affect the safety and stability of the bridge structure. Due to the presence of complexity in the scour mechanism, there is no common and simple method to estimate the scour depth. The present paper gives an idea of hybridizing two techniques such as an artificial neural network with swarm intelligence technique particle swarm optimization to estimate the scour depth around the bridge pier and abbreviated as PSO-ANN. The present discussion covers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results showed that the model produced estimates of scour equilibrium depth with many fewer constants compared to the hidden layer of neural networks. Sreedhara et al (2019) investigated the prediction of scour depths near a pier bridge by a swarming group of bees based on a neural network and found that for clear water conditions, the PSO-ANN model method outperforms the artificial neural network model. Azmatullah (2012) examined gene expression programming to estimate scour depth downstream of sills.…”
mentioning
confidence: 99%
“…The results showed that the model produced estimates of scour equilibrium depth with many fewer constants compared to the hidden layer of neural networks. Sreedhara et al (2019) investigated the prediction of scour depths near a pier bridge by a swarming group of bees based on a neural network and found that for clear water conditions, the PSO-ANN model method outperforms the artificial neural network model. Azmatullah (2012) examined gene expression programming to estimate scour depth downstream of sills.…”
mentioning
confidence: 99%